Krishna
1

Step 1: Before going to do the problem, Find the knowns and unknowns in and note it down.

Step 2: Explore the given rule

            EXAMPLE: x_{n+1} = ax_n - 3

            Succeeding term = a (preceding term) - 3


Step 3: By using the given rule find the required terms (x_2, x_3,x_4...etc)

            NOTE: According to the given rule substitute the values to get the required

                        term.

            EXAMPLE: For an attempt to  find the x_3

                                x_{n+1} = ax_n - 3

                                      x_3 =  ax_2 - 3

             Substitute the values x_2  [ Calculate x_2 (x_2 = a - 3, take x_1 = 1 since n>1)] 

                                x_ 3 = a(a - 3) - 3

                                  x_3 = a^2 – 3a – 3

Step 4: Compare the result with the given answer, verify is it equating or not